Żelazo meteorytowe w starożytnym Egipcie przed okresem późnym - Napierała, Mateusz (Folia Praehistorica Posnaniensia, 2021)
The aim of the article is to present an unusual raw material, which is the meteorite iron and its specific status in the culture of ancient Egypt. The presentation of this extraordinary material, highlighting the features allowing to recognize it, the interpretation of the artifacts made of it (taking into account the physicochemical analyzes), and the development of the results of experimental works recreating the methods of its processing allow us to obtain the necessary information about the delineation of meteorite iron metallurgy in ancient Egypt up to the beginning of the Late Period. An important source for achieving the article’s goal are also texts. Text analysis highlights the ambiguity of the terminology used to describe meteorite iron. By reviewing the contexts of its use, they allow us to enrich knowledge about its metallurgy and help to characterize the status of this metal in the consciousness of the Egyptians.